Variation of 45S rDNA intergenic spacers in Arabidopsis thaliana - Havlová, Kateřina; Dvořáčková, Martina; Peiro, Ramon; Abia, David; Mozgová, Iva; Vansáčová, Lenka; Gutierrez, Crisanto; Fajkus, Jiří (Plant molecular biology, 2016)
Approximately seven hundred 45S rRNA genes (rDNA) in the Arabidopsis thaliana genome are organised in two 4 Mbp-long arrays of tandem repeats arranged in head-to-tail fashion separated by an intergenic spacer (IGS). These arrays make up 5 % of the A. thaliana genome. IGS are rapidly evolving sequences and frequent rearrangements inside the rDNA loci have generated considerable interspecific and even intra-individual variability which allows to distinguish among otherwise highly conserved rRNA genes. The IGS has not been comprehensively described despite its potential importance in regulation of rDNA transcription and replication. Here we describe the detailed sequence variation in the complete IGS of A. thaliana WT plants and provide the reference/consensus IGS sequence, as well as genomic DNA analysis. We further investigate mutants dysfunctional in chromatin assembly factor-1 (CAF-1) (fas1 and fas2 mutants), which are known to have a reduced number of rDNA copies, and plant lines with restored CAF-1 function (segregated from a fas1xfas2 genetic background) showing major rDNA rearrangements. The systematic rDNA loss in CAF-1 mutants leads to the decreased variability of the IGS and to the occurrence of distinct IGS variants. We present for the first time a comprehensive and representative set of complete IGS sequences, obtained by conventional cloning and by Pacific Biosciences sequencing. Our data expands the knowledge of the A. thaliana IGS sequence arrangement and variability, which has not been available in full and in detail until now. This is also the first study combining IGS sequencing data with RFLP analysis of genomic DNA.
Keywords: DNA, Ribosomal Spacer; Arabidopsis thaliana; repetitivní sekvence nukleových kyselin; Nucleolus organizer region; Chromatin Assembly Factor-1; mutace; genetická variace; rDNA rearrangements; Genetic Variation; Repetitive Sequences, Nucleic Acid; Mutation; Chromatin assembly factor; faktor 1 pro uspořádání chromatinu; Intergenic spacer; RNA ribozomální; RNA, Ribosomal; 45S ribosomal DNA; mezerníky ribozomální DNA; Arabidopsis